Bentuk Solidaritas Masyarakat Nelayan di Kelurahan Kesenden - Saeful R, Dadan; Achdiani, Yani; Abdullah, Mirna Nur Alia (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2019)
This study examines and analyzes the values contained in the tradition of nadran, particularly social values that can form a Community solidarity fishermen in Kelurahan of Kesenden. Analyzing the forms of social solidarity in the community of fishermen in Kelurahan of Kesende the city of Cirebon. This research used a qualitative approach and methods a descriptive analysis for mempaparkan research results. Data collection on this research uses techniques of observation, interview techniques, and study the documentation of a trusted parties. Informant research consists of Pillars of fishermen, the Chairman of Society, Kebayan, the chairman of nadran fishing communities in the region of southern Samadikun The results of this research show that the fishing community solidarity is formed from the existence of a consensus on social values, religious values, such as moral values, the values of truth, beauty and value are believed and trusted by the fishing communities in the nadran tradition, so the shape of the solidarity Community fishermen in the village of kesenden, that is a form of mechanical solidarity.